Le neuroscienze come strumento di “emersione” del diritto muto (TEST BioLaw Journal - Rivista di BioDiritto, 2017)
This article investigates how the neuroscientific studies can become useful to unveil the “mute” dimension of law and determine its “appearance”. It is not a coincidence that a sensible anthropologist such as Roderick MacDonald imagined law as an iceberg where its emerged peak, visible above the water, represents the written law, while the most substantial submerged part represents all the implicit and inferential aspects of the law. Looking at the historical reality, the image is far from being defined. After broadly rethinking some of Rodolfo Sacco's reflections about the existence of "mute law", here the following considerations attempt to highlight the importance that neurosciences could have in forming the theoretical basis of the sources of law by better defining the physiology of the regulatory production processes.
Keywords: Neurosciences; written law; mute law; regulatory production; sources of law